Pharmacokinetics and perioperative efficacy of intravenous ketorolac in dogs. Issue 6 (8th March 2013) - Cagnardi, P.; Zonca, A.; Gallo, M.; Villa, R.; Carli, S.; Beccaglia, M.; Fonda, D.; Ravasio, G.
Abstract : Ketorolac (KET) is a nonsteroidal anti‐inflammatory drug approved for the use in humans that possesses a potent analgesic activity, comparable to morphine, and could represent a useful tool to control acute pain also in animals. The clinical efficacy and pharmacokinetic profile of intravenous (IV) ketorolac tromethamine (0.5 mg/kg) were studied in 15 dogs undergoing gonadectomy. Intra‐operative cardiorespiratory variables were monitored, and post‐operative pain was assessed using a subjective pain score (0–24) in all dogs, whereas the pharmacokinetic profile of the drug was determined in 10 animals. During surgery, mean minimal alveolar concentration of isoflurane was 1.69 ± 0.11%, and normocapnia and spontaneous ventilation were maintained in all animals. During pain assessment, no significant differences between males and females were found, and in no case rescue analgesia was necessary. No adverse effects were reported. Serum samples were purified by solid‐phase extraction and analysed by HPLC with UV‐Vis detection. A large variability was observed in serum concentrations. The kinetics of ketorolac was described by a noncompartmental analysis. The elimination half‐life (t½λz ) and Cl B were 10.95 ± 7.06 h and 92.66 ± 84.49 mL/h/kg, respectively, and V dss and V z were 1030.09 ± 620.50 mL/kg and 1512.25 ± 799.13 mL/kg, respectively. AUC(0→last) and MRT(0→last) were 6.08 ± 3.28 h × μg/mL and 5.59 ± 2.12 h, respectively. The results indicate that ketorolac possess good post‐operative analgesic effects until about 6 h after administration in dogs undergoing moderately painful surgery.